EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN BERBAGAI MODEL PENDEKATAN UNTUK MEREDUKSI PERILAKU MEMBOLOS SISWA - Siti Konaah; Risma Anita Puriani (JIP: Jurnal Ilmu Pendidikan, 2026)
Group counseling is a service available in guidance and counseling science that utilizes group dynamics of 6-8 people and aims to help alleviate student problems. This study aims to evaluate the effectiveness of group counseling services with various approaches. Researchers used a relevant literature study method in the 2019-2025 time period. The results of the study indicate that group counseling services with various approaches can minimize and reduce student truancy behavior. In addition, group dynamics can also encourage students to develop self-awareness, behavioral control, and responsibility in their learning activities. Therefore, researchers suggest that group counseling services can be an effective strategy for guidance and counseling teachers in helping overcome student truancy behavior at school.